Memória, processo e obra: a história de ela - Cardoso, Vanessa Karla Dias (2021)
“Memory, Process and Artwork: The Ela Story”, represents a double effort. It is, in the first place, a work in visual poetics, but it doesn't end there. It is also a research work in art, wich proposes to present the deviations of my own creative process in becoming-artwork, a notion that gives Deleuzian becoming a dimension that serves as a crack in the traps of repetitions, a artwork free of identities, wich result in my narrative artwork “The Ela Story”.